Stimulation of calvarial bone healing with human bone marrow stromal cells versus inhibition with adipose-tissue stromal cells on nanostructured β-TCP-collagen. (August 2018) - Bothe, Friederike; Lotz, Benedict; Seebach, Elisabeth; Fischer, Jennifer; Hesse, Eliane; Diederichs, Solvig; Richter, Wiltrud
Graphical abstract: Abstract: Bioactive functional scaffolds are essential for support of cell-based strategies to improve bone regeneration. Adipose-tissue-derived-stromal cells (ASC) are more accessible multipotent cells with faster proliferation than bone-marrow-derived-stromal-cells (BMSC) having potential to replace BMSC for therapeutic stimulation of bone-defect healing. Their osteogenic potential is, however, lower compared to BMSC, a deficit that may be overcome in growth factor-rich orthotopic bone defects with enhanced bone-conductive scaffolds. Objective of this study was to compare the therapeutic potency of human ASC and BMSC for bone regeneration on a novel nanoparticulate β-TCP/collagen-carrier (β-TNC). Cytotoxicity of β-TCP nanoparticles and multilineage differentiation of cells were characterized in vitro . Cell-seeded β-TNC versus cell-free controls were implanted into 4 mm calvarial bone-defects in immunodeficient mice and bone healing was quantified by µCT at 4 and 8 weeks. Tissue-quality and cell-origin were assessed by histology. β-TNC was non-toxic, radiolucent and biocompatible, lent excellent support for human cell persistence and allowed formation of human bone tissue by BMSC but not ASC. Opposite to BMSC, ASC-grafting significantly inhibited calvarial bone healing compared to controls. Bone formation progressed significantly from 4 to 8 weeks only in BMSC and controls yielding 5.6-fold more mineralized tissue in BMSC versus ASC-treated defects. Conclusively, β-TNC was simple to generate, biocompatible, osteoconductive, and stimulated osteogenicity of BMSC to enhance calvarial defect healing while ASC had negative effects. Thus, an orthotopic environment and β-TNC could not compensate for cell-autonomous deficits of ASC which should systematically be considered when choosing the right cell source for tissue engineering-based stimulation of bone regeneration. Statement of Significance: Bone-marrow-derived-stromal cells (BMSC) implanted on bone replacement materials can support bone defect healing and adipose-tissue-derived-stromal cells (ASC) being more accessible and better proliferating are considered as alternate source. This first standardized comparison of the bone regeneration potency of human ASC and BMSC was performed on a novel nanoparticular β-TCP-enriched collagen-carrier (β-TNC) designed to overcome the known inferior osteogenicity of ASC. β-TNC was non-toxic, biocompatible and osteoconductive supporting human bone formation and defect-closure by BMSC but not ASC. Long-term cell-persistence and the distinct secretome of ASC appear as main reasons why ASC inhibited bone healing opposite to BMSC. Overall, ASC-grafting is at considerable risk of producing negative effects on bone-healing while no such risks are known for BMSC.